Biaxially Compressive Strain in Ni/Ru Core/Shell Nanoplates Boosts Li–CO2 Batteries. Issue 30 (16th June 2022) - Fan, Li; Shen, Haoming; Ji, Dongxiao; Xing, Yi; Tao, Lu; Sun, Qiang; Guo, Shaojun
Abstract: Regulating surface strain of nanomaterials is an effective strategy to manipulate the activity of catalysts, yet not well recognized in rechargeable Li–CO2 batteries. Herein, biaxially compressive strained nickel/ruthenium core/shell hexagonal nanoplates (Ni/Ru HNPs) with lattice compression of ≈5.1% and ≈3.2% in the Ru {10−10} and (0002) facets are developed as advanced catalysts for Li–CO2 batteries. It is demonstrated that tuning the electronic structure of Ru shell through biaxially compressive strain engineering can boost the kinetically sluggish CO2 reduction and evolution reactions, thus achieving a high‐performance Li–CO2 battery with low charge platform/overpotential (3.75 V/0.88 V) and ultralong cycling life (120 cycles at 200 mA g −1 with a fixed capacity of 1000 mAh g −1 ). Density functional theory calculations reveal that the biaxially compressive strain can downshift the d‐band center of surface Ru atoms and thus weaken the binding of CO2 molecules, which is energetically beneficial for the nucleation and decomposition of Li2 CO3 crystals during the discharge and charge processes. This study confirms that strain engineering, though constructing a well‐defined core/shell structure, is a promising strategy to improve the inherent catalytic activity of Ru‐based materials in Li–CO2 batteries. Abstract : Biaxially compressive strained nickel/ruthenium core/shell hexagonal nanoplates are developed as advanced catalysts to boost the performance of lithium–carbon dioxide batteries. It is demonstrated that strain effect can tune the electronic structure of ruthenium, which makes the strained ruthenium shell energetically beneficial for the nucleation and decomposition of lithium carbonate crystals.